My life in safety lessons in performance improvement - Krishna M. Bala 1955- (Gerakbudaya Enterprise, 2021)
In the journey to improve performance in the field of safety, it is a sobering reality that input does not always equal output. That is the unique and ever-present challenge faced by leaders, managers and safety professionals in any industry that has a significant element of operational risk - industries where workers' lives are at stake. In a novel approach to addressing this dilemma, My Life in Safety treats this as a change management project, requiring synergy between people, plant and process to deliver the desired outcomes. What it offers is a tried and tested mental model that enables a systematic approach to the attainment of the ultimate objective of achieving "Zero". The Flow consists of a framework of tools, synthesising the author's four decades in operational, transformational and safety roles. It is a short and light read in a chatty personal style with concepts supported by the author's experiences and insights.